STRATEGI KOMUNIKASI PENUTUR ANAK DALAM INTERAKSI DENGAN BERBAGAI MITRATUTUR PADA LINGKUNGAN MASYARAKAT DIGLOSIK - Dyah Werdiningsih (LITERA, 2010)
This study aims to describe characteristics of child speakers’ communication strategies in their interaction with a variety of interlocutors in a diglossic society. This study was a longitudinal study involving subjects aged 2 – 5 years. The data were collected through observations, recording with an electronic recorder, and field note cards. The data were analyzed using the performance analysis technique. The findings show that characteristics of child speakers’ communication strategies in their interaction with a variety of interlocutors in a diglossic society appear in the types and type variations, causes, and functions of the use in the process of naturallyacquiring the pragmatic competence.